Epidemiologic Characteristics of Patients Presenting with Head Injury due to Road Traffic Accident and Factors Associated with Outcome: Experience of a Tertiary Care Center in Northern Kerala - Rajeev, Mandaka Parambil; Shinihas, Vattaparambil; Chauhan, Pankaj Singh (Indian Journal of Neurosurgery, 2019)
Background In India, most factors related to road traffic accident (RTA) causation and outcome go improperly documented, and database regarding RTA-related traumatic brain injury (TBI) seems inadequate. Two-wheeler drivers form the largest segment of people affected by RTA. The socioeconomic and neurologic burden, imposed by TBI due to RTAs (largely preventable), is overwhelmingly significant, especially for a developing country like India.Materials and Methods Descriptive study involving patients, presenting to the casualty of Government Medical College, Kozhikode, Kerala, was performed, and various demographic features were analyzed. Usage of helmet and history of alcohol intake were also noted. Patients were evaluated according to their presenting Glasgow coma scale (GCS), investigated and either operated or managed conservatively, and their outcome was assessed with Glasgow outcome score (GOS) at 3 months.Results Bike drivers formed the single largest proportion of RTA victims (53.7%). Proportion of helmet users was 17.9%, whereas 21.9% were found with history of alcohol intake. There was a consistent trend toward a favorable outcome in patients with no alcohol intake (17.08% deaths compared with 34.07% patients with alcohol intake) and with helmet usage (14.55% compared with 22.18% in patients without helmet). However, the absolute contribution of these factors cannot be inferred.Conclusion Various factors related to RTA need evaluation for pooling and compilation of data at regional and national levels. Mandatory helmet laws and strict implementation and provision of subsidized helmets (standard, full coverage) will go a long way in reducing the burden on limited health resources.
Keywords: road traffic accident; helmet; alcohol